MEDICAL IMAGE ENHANCEMENT BY FILTERS AND EDGE APPROACHES: REVIEW - Bir, Sukhwinder (International Journal of Psychosocial Rehabilitation, 2013)
Medical image enhancement improves the quality and facilitates diagnosis This thesis investigates seven methods of medical image enhancement by exploiting useful edge information Since edges have higher perceptual importance the edge information based enhancement process is interesting However determination of edge information is not an easy job In enhancement methods have limitations such as i Less effective for medical images containing wide range of anisotropic and directional features. Enhancement techniques have been widely used in the field of medical image processing, where the subjective quality of images is important for human interpretation and diagnosis. Various enhancement algorithms have developed to apply medical imaging problems. Since edges are higher perceptual importance, the primary objective of this thesis work is to develop and analyze edge information based methods to enhance the medical images.